Ferranti Effect in Transmission Line - Gagari Deb (Institute of Advanced Engineering and Science, 2012)
A temporary overvoltage is an oscillatory phase to ground or phase to phase over voltage that is relatively long duration and is undamped or only weakly damped.Temporary over voltages usually originate from faults, sudden charge of load, Ferranti effect, linear resonance, ferroresonance, open conductor, induced resonance from coupled circuits and so forth.The steady voltage at the open end of an uncompensated transmission line is always higher than the voltage at the sending end.This phenomenon is known as the Ferranti effect. This paper presents a study of Ferranti effect in electrical transmission line.The study is based on both software and hardware.The MATLAB program gives the locus of sending end voltage with line length which shows that receiving end voltage is greater than sending end voltage.From the experiment with transmission line simulator the values of three phase voltages at sending end and receiving end were found which proves the Ferranti effect.These two methods were used to give the idea about the Ferranti effect.DOI:http://dx.doi.org/10.11591/ijece.v2i4.451